Advances in atomic and molecular physics. Volume 15 - Bates, David R. (David Robert), 1916-1994.; Bederson, Benjamin; ScienceDirect eBooks (New York : Academic Press, 1979)
ADV IN ATOMIC & amp; MOLECULAR PHYSICS V15.
XI. Influence of Different Forms of Energy upon ReactivityXII. Translational Thresholds; References; Chapter 7. Ion-Atom Charge Transfer Collisions at Low Energies; I. Introduction; II. Symmetrical Resonance Processes; Ill. Nonresonant Atomic Charge Transfer Processes; IV. Total Cross Sections of Pseudocrossing Atomic Charge Transfer Processes; V. Curve-Crossing Spectroscopy; VI. Charge Transfer Processes of Excited Ions; References; Chapter 8. Aspects of Recombination; I. lntroduction; II. Radiative e-O+ Recombination and the Nightglow; III. Complex Ions.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Molecules; Atoms; SCIENCE -- Physics -- Quantum Theory; Atoms; Molecules; Electronic books